Projetos de dosadores mecânicos e pneumáticos para a semeadura mecanizada de amendoim - Angelo, Eduardo Prisco (Universidade Federal de São Carlos, 2020)
A crop of peanuts (Arachis hypogaea L.) is providing important gains for the country. However, although there has been an increase in the area sown in the country over the years, the need to increase also increases. For this, the development of mechanisms for specific use for culture is of great importance, since the use of standard dials for culture can favor mechanical injuries and failures in seed exposures. In this context, the objective of this work was to design two peanut seed engines. With a characterization of the linear and physical parameters of the seeds, it was possible to determine the mechanics of filling the discs for the honeycomb disk, and with the data of sowing densities (12; 15; 17 and 20 seeds m-1) with frequency of seed displacement. machine (4.00; 5.00 and 6.00 km h-1) determined a negative pressure in the pneumatic system. According to the analysis of the packing mechanics of the alveoli, the tangential speed of the base or alveolar disk must contain to dose as the three varieties were 43.65 rpm. On the other hand, with the determination of the negative pressure it was possible to verify that there is a variation of approximately 10.4 kPa of pressure between the lowest and the highest average speed of 4.0 km h-1 in relation to the number of seeds per meter , for working speeds of 5.0 and 6.0 km h-1 as media variations were 16.4 and 22.7 kPa, respectively. In this way, the standards used for dimensioning the mechanisms were dimensioned linear and an area designed for seeds. The processors' engines did not elaborate any AutoCAD® software and those printed using a 3D printer.
Projects of mechanical and pneumatic dosers for mechanized sowing of peanut
Keywords: Arachis hypogaea L; AutoCAD; Projetos de máquinas agrícolas; Arachis hypogaea L; AutoCAD; Agricultural machinery project; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA